Pengaruh Motivasi Kepuasan Kerja Pendidikan dan Pengalaman Kerja Terhadap Kinerja Guru SD Rantau Selatan di Labuhanbatu - Adelfina Adelfina; Ayi Darmana; Tita Rosita (Mahesa Research Center, 2022)
This study aims to analyze whether there is an influence of motivation on teacher performance, analyze whether there is an effect of job satisfaction on teacher performance, analyze whether there is an influence of education on teacher performance, analyze whether there is an influence of work experience on teacher performance and to analyze whether there is an influence of motivation, satisfaction work, education, and work experience on teacher performance. This research was conducted in elementary schools throughout Rantau Selatan in Labuhanbatu. Sampling using Multistage random sampling with criteria using purposive sampling (self choice) and by means of Cluster Random Sampling (CRS). The instrument used is a questionnaire. The questionnaire instrument in the form of a Likert scale with the number of motivational questionnaire items is 20 items, job satisfaction is 12 items and teacher performance is 20 items. The data analysis technique used assumption test in the form of univariate test, while hypothesis test used multivariate test at significant level a=0.05. The results showed that: There is an effect of motivation, job satisfaction, education, and work experience on teacher performance seen by the value of Fcount (3.302) > Ftable (2.55) significant value 0.017 <0.05, and R square value of 0.203